Synergistic Valorization of Palm Oil Mill Effluent and Boiler Ash into a Nutrient-Rich Liquid Organic Fertilizer - Irwan Taslapratama; Intan Permata Hati; Elfi Rahmadani; Ervina Aryanti; Fauziah Shahul Hamid; Bernardi Pranggono; Mishbahuddin (Indonesian Journal of Environmental Management and Sustainability, 2026)
Industrial symbiosis presents a transformative pathway for the sustainable management of palm oil byproducts. This study investigates a novel integrated valorization approach using boiler ash as a multifunctional ameliorant in the anaerobic fermentation of palm oil mill effluent (POME). By leveraging the synergistic physicochemical properties of acidic POME and alkaline boiler ash, we developed a self-buffering system to produce high-value liquid organic fertilizer. Varying boiler ash concentrations (0, 45, 50, and 55 g/L) were evaluated to determine the optimal nutrient recovery and stabilization parameters. Results demonstrate that a dosage of 55 g/L is statistically superior, effectively neutralizing the system to a stable pH of 7.5 without synthetic additives. This treatment yielded a nutrient-dense product containing 3.93% total NPK and 12.42% organic carbon, surpassing the Indonesian Ministry of Agriculture Regulation No. 261/2019 standards. Safety analysis revealed a Pb concentration of 12.28 ppm, which is significantly below the maximum allowable threshold, confirming the product’s environmental compatibility. This research provides a scientifically grounded method for converting industrial waste into a fortified agricultural input, advancing circular economy principles and supporting national sustainability frameworks like the Indonesia Sustainable Palm Oil (ISPO) certification.